Pengaruh Celebrity Endorser Terhadap Keputusan Pembelian Wisatawan Yogyakarta Pada Produk Oleh-Oleh Jogja Scrummy - Chriswardana Bayu Dewa (Jurnal Manajemen, 2018)
This study aims to determine whether the celebrity endorser became one of the factors that influence consumer purchase decisions, especially consumers in Indonesia in general and in Yogyakarta in particular. The data in this study were obtained by distributing questionnaires to 100 respondents in each outlet Jogja scrummy. The data used are primary data sampling technique used is non-probability sampling. The hypothesis was tested using the program Structural Equation Model (SEM). The results showed that the celebrity endorsement positive influence on purchase decisions. Keywords: Celebrity endorser, purchase decisions